Could Urine pH be a New Parameter for Mortality? - Sahin Tutak, Ayse; Fındıklı, Hüseyin Avni (Progress in Nutrition, 2021)
Background: Full urine analysis is a simple and in expensive test that can be easily performed in almost all laboratories and provides extremely useful information. This study aimed to examine whether urinary pH has any prognostic role in respect of mortality in intensive care unit (ICU) patients. Methods: In this study, a retrospective examination of patients hospitalized in the Internal Diseases Intensive Care Unit between 2017-2018 at the Investigators' Hospital was performed. A total of 2100 patients were excluded, of which 563 met at least one of the exclusion criteria. Results: Age, the total length of hospital stay (TLSH), and mortality were significantly higher in the pH ≤ 5.5 group (p